The mediating effect of media on the relationship between consumer values and attitudes, self-identity, trust in the government, and consumerism practices among students of higher learning institutions - Dol, Nurazlina; Abu Bakar, Elistina; Md Jusoh, Zuroni; Muhammad Arif, Afida Mastura (Malaysian Consumer and Family Economics Association (MACFEA), 2021)
Nowadays, consumer issues are becoming more serious, especially those involving online fraud, such as scams. As a consumer, one should take precautions to protect oneself from encountering this problem. Consumerism practices are the key components that provide consumers with strong self-protection and positive attitudes. Students of higher learning institutions, a large group of mainly young people, play the roles of educated agents of change who may champion the interests of consumers in the future. The objective of this study is to investigate the impact of media agents as a mediating variable in the relationship between consumer attitudes and values, self-identity, trust in the government, and consumerism practices. The Social Cognitive Theory and the Consumer Socialization Theory were used in this study to achieve a deep understanding of the concept of consumerism practices. This study involved eight hundred students of higher learning institutions in Malaysia from ten institutes selected by randomised sampling. A questionnaire was created and used for purposes of data collection. Data analysis was conducted in Structural Equation Modeling (SEM) analysis using the Analysis of Moment Structural (AMOS) software. The results showed that media agents are partial mediators in the relationship between self-identity and consumerism practices and between consumer attitudes and consumerism practices. It was also found that consumer attitudes, consumer values, self-identity, and trust in the government have a direct and significant relationship with students’ consumerism practices. This study contributes to the theoretical expansion of consumerism practices and serves as a guide for relevant ministries, institutions of higher learning, and consumer associations in their efforts to implement educational activities and programs on consumerism.